2013
DOI: 10.2136/vzj2013.04.0072
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Coupled Hydromechanical Modeling of Water Infiltration into a Transversely Isotropic Unsaturated Soil Region

Abstract: The partial differential governing equation governing fluid infiltration into an unsaturated transversely isotropic porous medium was developed by considering mass conservation, Darcy's law, and the elastic deformability of the porous skeleton. Analytical solutions for two‐dimensional coupled infiltration in an unsaturated porous medium of finite extent were obtained using a Fourier transform technique. The analytical formulation was used to examine the two‐dimensional infiltration and evaporation problem for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…It is shown that the pore water pressure dissipation caused by the effect of boundary runoff on the boundary and the transpiration of roots can increase the FOS. Unlike one-dimensional simulation results provided by Wu et al [40], VS always slips when the duration is greater than the lower bound.…”
Section: Effect Of Vegetation Rootcontrasting
confidence: 71%
“…It is shown that the pore water pressure dissipation caused by the effect of boundary runoff on the boundary and the transpiration of roots can increase the FOS. Unlike one-dimensional simulation results provided by Wu et al [40], VS always slips when the duration is greater than the lower bound.…”
Section: Effect Of Vegetation Rootcontrasting
confidence: 71%
“…The RE describes multidimensional unsaturated flow (Wu et al, 2013;Duc et al, 2020). The 2D RE is written as:…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…Analytical methods for developing the solution to Richards' equation mostly rely on the use of linearization based on Gardner's model. Many articles used such an approach to study flow in an unsaturated zone with infiltration from a variety of surface water bodies (see, e.g., Huang and Wu, 2012;Wu et al, 2013;Wang and Li, 2015). Those articles neglected the presence of an underlying aquifer and treated its water table as the lower boundary with a condition of constant pressure head (e.g., Huang and Wu, 2012) or water content (e.g., Chen et al, 2001b).…”
Section: Introductionmentioning
confidence: 99%